Beyond geopoetics: For hybrid texts. Issue 1 (March 2021) - Cresswell, Tim
This commentary responds to Eric Magrane's welcome focus on the possibilities of 'climate geopoetics' as a way of accessing and thinking environmental crisis differently. It explores the problem of approaching the general through the particular and the affordances that poetry provides in making this leap. In addition, it questions the particular veneration of the poet and poem and, building on the experiments of both poets and academics, argues for the embrace of hybrid forms that transcends the poetry/non-poetry divide.